Peningkatan Hasil Belajar Siswa Pada Pembelajaran IPAS Menggunakan Model Think Pair Share (TPS) Berbantuan Google Sites di Kelas IV SDN 20 Sinapa Piliang Kota Solok - Khairiyah, Nizfa; Hamimah, Hamimah; Zahara, Leni; Fitri, Ummiatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the improvement in student learning outcomes in IPAS lessons using the Think Pair Share (TPS) model supported by Google Sites in the fourth-grade class at SDN 20 Sinapa Piliang, Solok City. This study is a Classroom Action Research (CAR) project using both qualitative and quantitative approaches. The study was conducted in two cycles, each comprising planning, implementation, observation, and reflection. The research subjects were 20 fourth-grade students at SDN 20 Sinapa Piliang in Solok City. Data collection techniques included both test and non-test methods, and data analysis was conducted using both qualitative and quantitative approaches. The results showed that the average score for the teaching module in Cycle I was 87.5% (B), which increased to 96.43% (SB) in Cycle II. The average score for teacher activities in Cycle I was 87.5% (B), increasing to 95% (SB) in Cycle II; the average score for student activities in Cycle I was 87.5% (B), increasing to 95% (SB) in Cycle II. Learning outcomes in the attitude aspect for Cycle I averaged 82.49 (C), increasing to 90.9 (B) in Cycle II; the knowledge aspect for Cycle I averaged 81.75 (C), increasing to 90.5 (B) in Cycle II; and the skill aspect for Cycle I averaged 83.30 (C), increasing to 91.64 (SB) in Cycle II. Thus, it can be concluded that the Think Pair Share (TPS) model supported by Google Sites can improve student learning outcomes in IPAS instruction in Grade 4 at SDN 20 Sinapa Piliang, Solok City.